Local structural investigation of hafnia-zirconia polymorphs in powders and thin films by X-ray absorption spectroscopy - Schenk, Tony; Anspoks, Andris; Jonane, Inga; Ignatans, Reinis; Johnson, Brienne S.; Jones, Jacob L.; Tallarida, Massimo; Marini, Carlo; Simonelli, Laura; Hönicke, Philipp; Richter, Claudia; Mikolajic, Thomas; et al. (Elsevier Ltd., 2019)
Despite increasing attention for the recently found ferro- and antiferroelectric properties, the polymorphism in hafnia- and zirconia-based thin films is still not sufficiently understood. In the present work, we show that it is important to have a good quality X-ray absorption spectrum to go beyond an analysis of the only the first coordination shell. Equally important is to analyze both EXAFS and XANES spectra in combination with theoretical modelling to distinguish the relevant phases even in bulk materials and to separate structural from chemical effects. As a first step toward the analysis of thin films, we start with the analysis of bulk references. After that, we successfully demonstrate an approach that allows us to extract high-quality spectra also for 20 nm thin films. Our analysis extends to the second coordination shell and includes effects created by chemical substitution of Hf with Zr to unambiguously discriminate the different polymorphs. The trends derived from X-ray absorption spectroscopy agree well with X-ray diffraction measurements. In this work we clearly identify a gradual transformation from monoclinic to tetragonal phase as the Zr content of the films increases. We separated structural effects from effects created by chemical disorder when ration of Hf:Zr is varied and found differences for the incorporation of the substitute atoms between powders and thin films, which we attribute to the different fabrication routes. This work opens the door for further in-depth structural studies to shine light into the chemistry and physics of these novel ferroelectric thin films that show high application relevance.
Björn Matthey (Fraunhofer IKTS, Dresden) is acknowledged for providing HfO2 and ZrO2 powders on short notice after DESY’s renowned customs office punished us. Parts of this research were carried out at Petra III at DESY, a member of the Helmholtz Association (HGF). The experiments on single Si:HfO2 thin film samples were performed at the CLAESS beamline at ALBA Synchrotron with the collaboration of ALBA staff. We would like to thank Edmund Welter for assistance (in using beamline P65) and DESY for enabling this research for proposal no. 20160591 and for travel support. T.S. acknowledges the German Research Foundation (DFG) for funding this work in the frame of the project “Inferox” (project no. MI 1247/11-2). B.J., J.L.J., and U.S. acknowledge funding from the Army Research Office through contract number W911NF-15-1-0593. This work was performed in part at the Analytical Instrumentation Facility (AIF) at North Carolina State University, which is supported by the State of North Carolina and the U.S. National Science Foundation (award number ECCS-1542015). The AIF is a member of the North Carolina Research Triangle Nanotechnology Network (RTNN), a site in the National Nanotechnology Coordinated Infrastructure (NNCI).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Extended X-ray absorption fine structure; X-ray absorption near edge structure; Ferroelectrics; Hafnium oxide; Zirconium oxide